Enhanced Urea Activity of Oxidation on Nickel‐Deposited Tin Dendrites. Issue 5 (15th February 2017) - Singh, Ramesh Kumar; Subramanian, Palaniappan; Schechter, Alex
Abstract: Urea oxidation has gained tremendous research interest, owing to its application in direct urea fuel cells and urea electrolyzers. In this work, the electrochemical oxidation of urea on a Ni/Sn dendrites catalyst is investigated. Ni and Ni/Sn dendrites are synthesized through electrodeposition on porous Toray © carbon paper. The prepared catalysts were characterized by scanning electron microscopy, X‐ray diffraction, and inductively coupled plasma−optical emission spectroscopy. The Ni/Sn dendrites oxidized 0.33 M urea in alkaline solution at an onset potential of 0.34 V vs. Ag/AgCl with a current density of 44 mA cm −2 @0.55 V, which is higher than that of electrodeposited Ni/TC (31 mA cm −2 @0.55 V). In situ Raman spectroscopic measurements indicate that urea oxidation on Ni/Sn dendrites is initiated by Ni(III)OOH species. Electrochemical impedance spectroscopy patterns of Ni/Sn dendrites in the presence of urea displayed a single depressed semicircle at potentials of 325 mV and two semicircles above 325 mV with a decreased total charge‐transfer resistance. The Ni/Sn dendrites electrode shows lower resistance at the tested potentials, indicative of faster urea oxidation kinetics. Abstract : Feeling active : Ni/Sn dendrites catalyst exhibits enhanced activity towards urea oxidation, owing to better dispersion of Ni on the Sn dendritic structure and improved charge‐transfer kinetics.